USING PEER COORECTIVE FEEDBACK TO IMPROVE STUDENTS’ WRITING IN RECOUNT TEXT - Suryanti, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: The aims of this study are to investigate how the peer corrective feedback (PCF) can improve the students’ writing recount text and what is the interaction mainly exists in PCF. This study is a classroom action Research with three cycles. The data were collected through observation during the treatment. The writing test conducted at the end of each cycle; the questionnaire had been distributed to the 29 students. A group interview was conducted to get deep verbal responses. The result found that the students’ interaction and attitudes were positive at the end of treatment. The students were more enjoyable when sharing the ideas with their peers. It wa because they used the same language and an informal situation without being afraid of making mistakes when discussing. The writing test showed the improvement at the end of every cycle. The interview data analysis indicated that the students were confident to write English and share their ideas with their peers. Related to the peer’s correction, the result was unclear and doubtful, therefore they preferred the teacher to give final correction. Key Words: Peer Corrective Feedback, Improving, Interaction Abstrak: Tujuan dari penelitian ini untuk mengetahui sejauh mana Peer Corrective Feedback dapat meningkatkan kemampuan siswa dalam menulis teks recount dan interaksi  apa yang muncul dalam PCF. Penelitian ini adalah penelitian tindakan kelas dengan tiga siklus, Data diperoleh dari pengamatan selama pembelajaran, tes tertulis dilakukan pada akhir setiap siklus, data kuesioner diambil dari 29 siswa, interview grup dilakukan untuk menggali lebih dalam lagi respon siswa terhadap penerapan PCF. Hasil dari penelitian ditemukan bahwa interaksi dan sikap siswa menunjukkan sikap positif pada setiap siklus pembelajaran. Siswa lebih senang ketika berbagi pendapat dengan teman sebaya karena mereka berkomunikasi dengan bahasa yang sejenis dan situasi yang tidak formal tanpa khawatir salah pada saat berdiskusi. Hasil dari tes tertulis juga menunjukkan peningkatan pada setiap siklus. Dari analisis data wawancara menunjukkan bahwa siswa sangat percaya diri dalam menulis Bahasa Inggris dan berbagi ide dengan teman sebaya. Sehubungan dengan hasil koreksian teman sebaya mereka berpendapat bahwa hasilnya kurang tepat dan meragukan, oleh karena itu mereka lebih cenderung apabila guru memberikan koreksian terakhir. Kata kunci: Peer Corrective Feedback, Peningkatan, Interaksi